2021
DOI: 10.3389/fgene.2021.664393
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Analysis of the Dysregulated ceRNA Network and Identification of Risk Long Noncoding RNAs in Breast Cancer

Abstract: Breast cancer (BRCA) is the second leading cause of cancer-related mortality in women worldwide. However, the molecular mechanism involved in the development of BRCA is not fully understood. In this study, based on the miRNA-mediated long non-coding RNA (lncRNA)–protein coding gene (PCG) relationship and lncRNA–PCG co-expression information, we constructed and analyzed a specific dysregulated lncRNA–PCG co-expression network in BRCA. Then, we performed the random walk with restart (RWR) method to prioritize BR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…During the research, we gathered 1019 differentially expressed arlncRNAs, and identified those with a prognostic value. We performed uni-and multi-Cox regression and LASSO regression, whereby seven arlncRNAs were validated for the construction of risk models, including UBE2Q1-AS1 that constituted a prognostic model for gastric cancer (27), `MAFG-DT`which was also a crucial member of the prognostic model for breast cancer (28), and AC112721.2 that regulated breast cancer expression through the TGF-b signaling pathway (29). Further studying these lncRNAs may provide a survival prediction.…”
mentioning
confidence: 99%
“…During the research, we gathered 1019 differentially expressed arlncRNAs, and identified those with a prognostic value. We performed uni-and multi-Cox regression and LASSO regression, whereby seven arlncRNAs were validated for the construction of risk models, including UBE2Q1-AS1 that constituted a prognostic model for gastric cancer (27), `MAFG-DT`which was also a crucial member of the prognostic model for breast cancer (28), and AC112721.2 that regulated breast cancer expression through the TGF-b signaling pathway (29). Further studying these lncRNAs may provide a survival prediction.…”
mentioning
confidence: 99%
“…The expression of another prognosis-related lncRNA AC011468.1 was repressed in Stage Ⅲ–Ⅳ, which is consistent with the report by Zhao et al (2021) . Also, AL354919.2, Z84484.1, PTOV1-AS2, and MAFG-DT were found to be associated with the prognosis of cancer patients in several studies ( Liu et al, 2021 ; Su et al, 2021 ; Wang et al, 2021 ; Zhao et al, 2021 ). Also, especially, AL354919.2 was obviously upregulated in low-grade BC patients.…”
Section: Discussionmentioning
confidence: 91%
“…Mammography has a variable rate of false positives ranging from 12% to 65%, which is responsible for the over-diagnosis of 31% of all breast cancer cases ( Nassar et al, 2017 ). Other imaging techniques such as MRI, ultrasound, CT, and PET are also accompanied by some limitations such as low sensitivity and specificity and being expensive ( Alyami, 2021 ; Su et al, 2021 ; Jin et al, 2021 ; Darbeheshti et al, 2022 ; Yousefi et al, 2022 ). As a result, it is deemed necessary to introduce new biomarkers that can overcome these limitations.…”
Section: Discussionmentioning
confidence: 99%